Chronic Inflammation in Cancer Development - Multhoff, Gabriele; Molls, Michael; Radons, Jürgen (Frontiers in Immunology, 2012)
Chronic inflammatory mediators exert pleiotropic effects in the development of cancer. On the one hand, inflammation favors carcinogenesis, malignant transformation, tumor growth, invasion and metastatic spread; on the other hand inflammation can stimulate immune effector mechanisms that might limit tumor growth. The link between cancer and inflammation depends on intrinsic and extrinsic pathways. Both pathways result in the activation of transcription factors such as NF-B, STAT-3, and HIF-1 and in accumulation of tumorigenic factors in tumor and microenvironment. STAT-3 and NF-B interact at multiple levels and thereby boost tumor-associated inflammation which can suppress anti-tumor immune responses. These factors also promote tumor growth, progression and metastatic spread. IL-1, IL-6, TNF and PGHS-2 are key mediators of an inflammatory milieu by modulating the expression of tumor-promoting factors. In this review we concentrate on the crucial role of pro-inflammatory mediators in inflammation-driven carcinogenesis and outline molecular mechanisms of IL-1 signaling in tumors. In addition, we elucidate the dual roles of stress proteins as danger signals in the development of anti-cancer immunity and anti-apoptotic functions.